2018
DOI: 10.3991/ijim.v12i3.8070
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Crime Mitigation of Mobile Application Users for Online Transportation

Abstract: Online transport service is currently popular in Indonesia. Not only provide ride-sharing service, but also other services such as food delivery, medicine delivery, and courier service. Ease of use and low cost make online transportation service more favored by consumers. However, this service has several disadvantages that cause inconvenience to the user until the occurrence of fraud action by the driver or the customer. Therefore identification of system deficiencies needs to be done to improve the security … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In Damaini et al [16] developed a fraud detection ranking system to get a better user experience based on rankings, ratings, and reviews. In this way, the two types of fraud are assisted by analyzing the user's comments and ratings on the application, and finally the three pieces of evidence are used to calculate the aggregation to evaluate the credibility of the application's leading session.…”
Section: Fraud Spam and Incentivized Reviews And Ratingsmentioning
confidence: 99%
“…In Damaini et al [16] developed a fraud detection ranking system to get a better user experience based on rankings, ratings, and reviews. In this way, the two types of fraud are assisted by analyzing the user's comments and ratings on the application, and finally the three pieces of evidence are used to calculate the aggregation to evaluate the credibility of the application's leading session.…”
Section: Fraud Spam and Incentivized Reviews And Ratingsmentioning
confidence: 99%
“…Accordingly, despite the advantages there was still mistrust concerning the company services on two levels: the legal gaps regarding such business models and trust in the procedural process of transporting people. Therefore, for several years Gojek operated with no significant growth (Damaini et al. , 2017) – not because of a lack of an economic value proposition, but due to a lack of trust from both the investor and the customer.…”
Section: About Gofoodmentioning
confidence: 99%
“…Based on the reviewed studies, it can be concluded that SD is suitable to be used to simulate the medium and long-run effect of varies transportation policies considering the influenced factors as a feedback interrelationship that work as a holistic model which changes cause to a chosen policy variable will effect on the other variable [24].…”
Section: System Dynamics Studies Related To Transportation Issuesmentioning
confidence: 99%